Penyuluhan Kewirausahaan Tentang Bisnis Keluarga kepada Perkumpulan Ibu-Ibu RT 12 Kota Banjarmasin - Dyah Sri Wulandari; Dewi Aina; Mirmaraditha Widyani; Yuliarti Rezeki; Ridha Nur Izzati (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
This Community Service is about Entrepreneurship Counseling About Family Business to the Women's Association of Rt. 12 Banjarmasin City. The problem faced by the residents of Kelayan A is that during the current pandemic, some residents have experienced layoffs and decreased income. The purpose of holding this entrepreneurship counseling is to help residents in dealing with these problems. As for how to diversify Haruan fish into shreds. The advantage of processing the product in the form of shredded fish is that the product can be more resistant. In terms of income, there is new income for residents of service A and this is very helpful for residents who do not have jobs because they are affected by Covid-19. The method in this service is by way of counseling and training. The first thing that was done was counseling about entrepreneurship and how to make haruan fish floss so that it could provide added value. Second, designing product packaging in order to increase prices and third, exposure on marketing methods both online and offline. The result of this entrepreneurship counseling is that the traders are very enthusiastic. The formation of a new group of entrepreneurs on a small scale is expected to increase in the future. Citizens also gain insight into better marketing. The conclusion from this activity is that there is an increase in the income of local residents.